The Influence of Celebrity Endorsers, Electronic Word of Mouth, and Lifestyle on Purchasing Decisions for Eiger Adventure Products (A Study on Eiger Adventure Consumers in Surabaya City) - Silvia Anisah Lubis; Budi Prabowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of celebrity endorsers, electronic word of mouth (e-WOM), and lifestyle on purchasing decisions for Eiger Adventure products. A quantitative approach was employed with data collected through questionnaires distributed to consumers who have purchased Eiger products. Multiple linear regression analysis was used to examine the effect of each variable. The findings show that simultaneously, celebrity endorsers, e-WOM, and lifestyle significantly influence purchasing decisions. However, partially, only celebrity endorsers and e-WOM have significant effects, while lifestyle does not. These findings highlight that promotional efforts through public figures and consumer reviews in digital media contribute more strongly to purchasing decisions than lifestyle factors. Therefore, companies are advised to maximize the role of endorsers and e-WOM strategies.